Maxillary aneurysmal bone cyst: Report of a rare case - Sheth M; Sujan S; Poonacha K (Wolters Kluwer Medknow Publications, 2010)
Everyone likes to see, hear, and know about rare things. An aneurysmal bone cyst (ABC) is an uncommon non-neoplastic lesion of the bone, mostly affecting long bones and spine. This rare jaw lesion usually affects the mandible but origin from the maxillary anterior region is even rarer. This paper describes a case of an ABC in an 8-year-old female child with a progressively increasing swelling in the right nasomaxillary region developed over a period of 1.5 months. Treatment consisted of the excision and enucleation of the lesion through an intraoral approach under general anesthesia. The higher prevalence in young adulthood has made the role of pedodontists vital in diagnosing ABCs, at the earliest.